Comparison of the Effects of Core Stability and Trampoline Exercises on Static and Dynamic Balance, and Ankle Proprioception in Female Volleyball Players with Chronic Ankle Instability - Fatemeh Bahrami; Mahdi Sabbagh Langeroudi (Biyumikānīk-i varzishī, 2023)
Objective This study sought to compare the impact of core stability and trampoline training on the static and dynamic balance, along with proprioception, among female volleyball players dealing with chronic ankle instability. Methods TThirty-six female volleyball players experiencing chronic ankle instability were purposefully chosen and randomly split into three groups: core stability training, trampoline training, and a control group. Static and dynamic balance were assessed using the stork and Y balance tests, while proprioception was evaluated utilizing a goniometer. Following the pre-test evaluations, the core stability and trampoline training groups underwent a 6-week exercise regimen. Post this training period, further evaluations were conducted. The ANCOVA test, LSD, and paired t-tests were employed for inter-group comparisons and intra-group assessments. Results Findings suggest that both training programs significantly impacted static balance (p≤0.01), dynamic balance (p≤0.01), and ankle proprioception in dorsiflexion (p≤0.01) and plantar flexion (p≤0.01) positions. Notably, a notable difference was observed between the effects of the two training programs on posterior-medial orientation, total dynamic balance score, and proprioception in plantar flexion. However, the trampoline training program demonstrated a greater effect than the core stability program. Nevertheless, no significant difference was found between the two training groups in static balance, anterior and posterior-lateral dynamic balance, and proprioception in dorsiflexion (p>0.05). Furthermore, both training groups exhibited significant differences in the researched variables when compared to the control group (p≤0.01). Conclusion Overall, the results illustrate that incorporating core stability exercises and trampoline training enhanced static and dynamic balance, as well as deep ankle sensation, among athletes dealing with chronic ankle instability.